2008
DOI: 10.1364/oe.16.002302
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric functions of a growing silver film determined using dynamic in situ spectroscopic ellipsometry

Abstract: The dielectric functions of plasma deposited silver on SiO2 through all stages of Volmer-Weber growth at room temperature and 150 degrees C were determined unambiguously by applying a model-independent inversion method to dynamic in situ spectroscopic ellipsometric data. The results show large differences in the localized plasmon resonance and the percolation threshold at the two temperatures. Using these model-independent dielectric functions we assess the effectiveness of modelling the plasmon resonance by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…45 Therefore, v = 10 11 S −1 for room-temperature deposition, or v = 10 13 S −1 for deposition around 500°C. Shklyav et al 41 calculated and observed an island density of n = 10 12 cm −1 for Ge on SiO 2 deposition performed in the 500°C range; therefore, we would expect an island density of approximately n = 10 12 × 500/25 = 2 × 10 13 cm −1 for our room-temperature deposition. It has been reported 46 that Ge atoms segregate into Ag grain boundaries and tend to concentrate on the Ag free surface due to grain boundaries of Ag films providing sites where Ge solute atoms have lower Gibbs free energy than on the Ge-SiO 2 interface.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…45 Therefore, v = 10 11 S −1 for room-temperature deposition, or v = 10 13 S −1 for deposition around 500°C. Shklyav et al 41 calculated and observed an island density of n = 10 12 cm −1 for Ge on SiO 2 deposition performed in the 500°C range; therefore, we would expect an island density of approximately n = 10 12 × 500/25 = 2 × 10 13 cm −1 for our room-temperature deposition. It has been reported 46 that Ge atoms segregate into Ag grain boundaries and tend to concentrate on the Ag free surface due to grain boundaries of Ag films providing sites where Ge solute atoms have lower Gibbs free energy than on the Ge-SiO 2 interface.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…20,[24][25][26]29,30,46 The samples were subsequently measured more extensively ex situ with a J. A. Woollam Co., Inc. VASE system to collect angle-and energy-resolved VAMM and scattering spectra.…”
Section: Acs Photonicsmentioning
confidence: 99%
“…As examples of recent applications of spectroscopic ellipsometry: The dielectric functions of plasma deposited silver on SiO 2 through all stages of Volmer-Weber growth at room temperature and 150 C were determined unambiguously by applying a model-independent inversion method to dynamic in situ spectroscopic ellipsometric data (Oates et al 2008).…”
Section: Introductionmentioning
confidence: 99%